Testing a new reinforced brick masonry shell system - Barros, Joaquim A. O. (2007)
The main aim of the current paper is to describe the experimental research carried out at the University of Minho, Portugal, regarding the development of an innovative reinforced brick masonry shell structural system. The concept of the system is based on the work of the engineer Eladio Dieste, and focuses on the prefabrication industry. The structural system is composed of a layer of clay bricks, reinforced concrete joints and a reinforced concrete cover layer. The constituent materials of the structural system were selected according to the necessary requirements in terms of mechanical properties and prefabrication technology. To analyse the interaction between the intervening materials, flexural, shear and biaxial tests with representative panels were carried out. To validate the developed structural system, a full scale shell was built and tested under monotonic vertical load applied at a quarter of its span. The shell performance revealed that the developed structural system is suitable for the proposed application.